Riverfront remediation: redevelopment for human access and wildlife health - Swehla, Tyler (Kansas State University, 2017)
Historically, industrial riverfronts often polluted waters and sites with chemicals, leading to degraded ecosystem health and reduced numbers of aquatic wildlife downstream. These sites currently pollute the environment through residual chemicals and waste left behind by industrial-era production factories. Urban riverfront redevelopment offers many possibilities to restore wetland ecosystems and reestablish site connections to surroundings through human access. By redeveloping urban rivers for wetland protection and stormwater management, cities can begin to regain their connections with the landscape while providing resilient ecosystems through restoration. This proposal identifies possibilities for riverfront redevelopment as wetlands and tools for restorative action aiding increased human access and wildlife health. A stormwater management plan utilizing phytotechnology is proposed for the ARMCO Site at 7000 Winner Rd. Kansas City, MO, a former steel manufacturing site, adjacent to the Missouri River and Blue River waterways. Using plant material and landscape design, the ARMCO riverfront has been redesigned to unlock the full potential of treatment wetlands and showcase emerging treatment methods that could soon become typical cleanup procedure. A template for remediation design has been created with the techniques identified for remediation, stormwater treatment, and habitat creation outlined in the master plan proposal. Nine precedent studies have been used to identify key concepts for design phasing aimed at human accessibility and modifications of restorative tools. Careful deliberation of stormwater containment and flood plain levels define site layout while contributing design responses adaptable for year-round functionality coupled with landscape interest for each season. The techniques and planting palette have been tailored to address the specific site contaminants for the Missouri River riverfront but are adaptable for various contaminants and ecosystems.
Keywords: Phytoremediation; Riverfront; Stormwater management; Habitat creation; Wildlife health; Kansas City